2002
DOI: 10.1002/zoo.10039
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids, vitamin A, and vitamin E concentrations during egg development in panther chameleons (Furcifer pardalis)

Abstract: Insects are known to be poor sources of preformed vitamin A, leading to the speculation that insectivorous species, including reptiles, may be able to convert carotenoid precursors to meet dietary requirements for this nutrient. This study was conducted to indirectly evaluate carotenoid and vitamin A metabolism in the panther chameleon (Furcifer pardalis). Eggs were obtained from females in Madagascar that were yolked either early or later in the breeding season, and carotenoid (α-and β-carotene, cryptoxanthin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…It is assumed that the concentrations in groups UV and No originated from low levels of vitamin A in untreated locust nymphs and potentially from the conversion of b-carotenes (not determined in this study) from the gut contents of these locusts. It has been suggested that insectivores may benefit from carotenoids that can be converted when required (39). Hence, a combination of preformed vitamin A and carotenoids may be optimal for veiled chameleons.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that the concentrations in groups UV and No originated from low levels of vitamin A in untreated locust nymphs and potentially from the conversion of b-carotenes (not determined in this study) from the gut contents of these locusts. It has been suggested that insectivores may benefit from carotenoids that can be converted when required (39). Hence, a combination of preformed vitamin A and carotenoids may be optimal for veiled chameleons.…”
Section: Discussionmentioning
confidence: 99%
“…Many oviparous species transfer carotenoids to the egg yoik (e.g., fish lAndo and Hatano 1991 ], reptiles [Dierenfeld et al 2002], and birds ISurai et al 1998]). Little is known, however, about the underlying mechanisms of maternal transfer of tbe pigments to the developing oocytes.…”
Section: Physiological and Biochemicalmentioning
confidence: 99%
“…In particular, carotenoid pigments obtained from plants, algae, some bacteria and fungi (Gray 1996) perform important biological functions in animal tissues, such as the development of the intense pigmentation of many sexual ornamentations, or the enhancement of the antioxidant activity and the immune system (Aguilera & Amat 2007;Fitze et al 2007). Moreover, carotenoids are the essential precursors of vitamin A (Pitt 1971), which is involved in many vital functions as growth, vision, cell differentiation and spermatogenesis (Dennert 1984;Underwood 1984;Dierenfeld et al 2002).…”
Section: Introductionmentioning
confidence: 99%